Cervicometría previa a la inducción del trabajo de parto como predictor del tiempo de dilatación. - Herrera Figueroa, Andrés Fernando (2015)
The importance of cervicometría prior of labor is to predict how how can conclude the same. To carry out this research work I determine cervical length by transvaginal ultrasound before induction of labor and relate time cervical dilation in patients treated at the Gynecology-Obstetrics Ollague Angela De Loayza Hospital in the period January-June 2015; determine cervical length of selected patients; compare cervical length after induction of labor with cervical dilation time; establish cervical length can predict dystocia cervical dilation. An observational study Analytical Transversal Cutting was performed in all patients treated at the Gynecology-Obstetrics Hospital Loayza Angela De Ollague for the period January-June 2015, obtaining the following results: Measurement of cervical length has a directly proportional to the time of cervical dilation relationship involved, the higher cervical length, longer cervical dilation. It is argued that the transvaginal ultrasound is a reliable method for predicting the time of cervical dilation and concludes that a cervical length of 26 mm or more was associated with increased cervical dilatation time (12 or more hours), finding statistically significant ( p = 0.000). Keywords: cervix, Measurement, Induction, Childbirth